PENERAPAN METODE PEMBIASAAN DALAM PELAKSANAAN SHALAT DHUHA BERJAMA’AH TERHADAP PENDIDIKAN KARAKTER DISIPLIN SISWA DALAM BERIBADAH DI MTsN 2 AGAM - Hotma Sormin; M. Isnando Tamrin; Rismayeni Rismayeni (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The dhuha prayer is one of the sunnah prayers whose law is to perform/perform it, namely the sunnah sukakad (highly recommended). Dhuha prayer is a sunnah prayer that is performed when the sun is rising, around 7 am until midday time. The dhuha prayer is performed for a minimum of 2 rak'ahs, it can also be 4, 6 or 8 rak'ahs. So that students can be disciplined in carrying out the Dhuha prayer, it is necessary to apply a habituation method in its implementation. It is hoped that this article can become a form of scientific literacy that can be used as motivational material for other schools. The research methodology used in this research is a descriptive qualitative approach and to collect research data, researchers carry out interviews, observations, document analysis, or case studies that occurred at the research location.